2022
DOI: 10.1002/adma.202205763
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered Unparalleled Strength and Supertoughness of Poly(urea‐urethane) with Shape Memory and Clusterization‐Triggered Emission

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…[40] Therefore, optimization of the strength and distribution of the hydrogen-bonding interactions inside PU elastomers is envisaged as a feasible approach to further improve the mechanical properties. [41] In addition to the high mechanical strength, other properties (e.g., degradability, biosafety) may also be important for some special applications in the biomedical field. Construction of the biodegradable PU elastomers with extremely high mechanical strength and toughness is still urgently desired.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Therefore, optimization of the strength and distribution of the hydrogen-bonding interactions inside PU elastomers is envisaged as a feasible approach to further improve the mechanical properties. [41] In addition to the high mechanical strength, other properties (e.g., degradability, biosafety) may also be important for some special applications in the biomedical field. Construction of the biodegradable PU elastomers with extremely high mechanical strength and toughness is still urgently desired.…”
Section: Introductionmentioning
confidence: 99%
“…The D value for PU ‑HMDI‑200% is bigger than that for PU ‑HMDI‑0% due to the dissociation of H-bonding and expansion of entangled molecular chains along with the increase in strain. However, the intensity of the scattering peak is weaker because the dissociation of H-bonding during stretching altered the microstructure, leading to attenuating microphase separation …”
Section: Resultsmentioning
confidence: 99%
“…The systolic and diastolic function of mimosa is attributed to a periodic nanostructure . Inspired by natural structural materials, many groundbreaking research studies have been reported, such as record-high mechanical robustness of poly­(urethane-urea) elastomers, artificial muscle fibers, and reversible morphing hydrogels . These high-performance and multifunctional shape-changing polymers are promising in soft actuators, artificial muscles, biological medical devices, and large self-unfolding structures in extreme environments.…”
Section: Introductionmentioning
confidence: 99%
“…Luminescent materials have received increasing interest due to their versatile applications in biomedical and engineering fields. Particularly, room-temperature phosphorescence (RTP), featuring a long persistent afterglow and a large Stokes shift under mild conditions, is important for the design of advanced optical materials with great potential in information security, bioimaging, chemical sensing, etc. A conventional strategy is to incorporate molecular chromophores into polymers and elastomers for RTP; however, these chromophores often have aromatic groups and require sophisticated design and organic synthesis. In recent years, polymeric phosphors with clusterization-triggered emission (CTE) properties are recognized as an emerging class of RTP materials and have attracted tremendous attention. These materials are usually metal-free and contain no aromatic groups as the luminescent centers. Their nonconjugated electron-rich groups (e.g., carbonyl) are nonluminescent in the isolated state; however, while they are clustered, through-space conjugation induces extended electron delocalization that results in lowered energy gaps and finally the clusteroluminescence. This unique mechanism affords CTE-based polymeric phosphors with many attributes such as easy preparation and tunable RTP properties. , However, CTE-based polymeric phosphors are sensitive to environmental conditions and easily quenched. , When exposed to a good solvent such as in a gel state, the hydration of polymers and swelling of networks cause cluster disaggregation and increased flexibility of polymer chains, leading to enhanced nonradiative decay and reduced fluorescence and phosphorescence.…”
Section: Introductionmentioning
confidence: 99%